Workforce outcomes among substance use peer supports and their contextual determinants: A scoping review protocol. - Justin S Bell; Tina Griffin; Sierra Castedo de Martell; Emma Sophia Kay; Mary Hawk; Michelle Hudson; Bradley Ray; Dennis P Watson (PLoS ONE)
Introduction Peer recovery support services are a promising approach for improving harm reduction, treatment, and recovery-related outcomes for people who have substance use disorders. However, unique difficulties associated with the role may place peer recovery support staff [i.e., peers] at high risk for negative workforce outcomes, including burnout, vicarious trauma, and compassion fatigue. Objective This scoping review protocol aims to describe a proposed effort to review the nature and extent of research evidence on peer workforce outcomes and how these outcomes might differ across service settings. Results of the review described in this protocol will help to answer the following research questions: 1) What is known about workforce-related outcomes for peers working in the substance use field?; 2) What is known about how the structure of work impacts these outcomes?; and 3) How do these outcomes differ by service setting type? Methods A scoping review will be conducted with literature searches conducted in PsycINFO®, [EBSCO],Embase® [EBSCO], CINAHL® [EBSCO], Web of Science™ [Clarivate], and Google Scholar databases for relevant articles discussing US-based research and published in English from 1 January 1999 to 1 August 2023. The proposed review will include peer-reviewed and grey-literature published materials describing the experiences of peers participating in recovery support services and harm reduction efforts across a variety of service settings. Two evaluators will independently review the abstracts and full-text articles. We will perform a narrative synthesis, summarizing and comparing the results across service settings. Expected outputs Publishing this protocol will help accelerate the identification of critical workforce issues, and bolster the transparency and reporting of the final review. The proposed review will assess the state of the literature on peer workforce-related outcomes and how outcomes might vary by service setting context. Results of the proposed review will be disseminated in peer-reviewed publications and conference presentations. Findings will inform the field regarding future directions to support the emerging peer workforce. Trial registration Systematic review registration Submitted to Open Science Framework, August 22nd, 2023.